2021
DOI: 10.2967/jnumed.120.256081
|View full text |Cite
|
Sign up to set email alerts
|

Hypermetabolism on Pediatric PET Scans of Brain Glucose Metabolism: What Does It Signify?

Abstract: When interpreting clinical 2-deoxy-2[ 18 F]fluoro-D-glucose (18F-FDG) positron emission tomography (PET) scans of the brain (excluding tumors) in children, the typical abnormality is hypometabolism of various brain regions. Focal areas of hypermetabolism are noted occasionally and the usual interpretation is that the hypermetabolic region represents a seizure focus. In this review, we discuss and illustrate the multiple causes of hypermetabolism that should not be interpreted as seizure activity could potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The high concentration of mitochondria in basal ganglia neurons predisposes them to ischemic damage [ 22 ]. It has been already demonstrated that basal ganglia and thalami may be particularly affected by hypoxia in children and neonates [ 23 , 24 ]. In both children and adults, hypoxic-ischemic encephalopathy almost invariably causes bilateral and symmetrical damage, often affecting the basal ganglia [ 25 ], as observed in our patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The high concentration of mitochondria in basal ganglia neurons predisposes them to ischemic damage [ 22 ]. It has been already demonstrated that basal ganglia and thalami may be particularly affected by hypoxia in children and neonates [ 23 , 24 ]. In both children and adults, hypoxic-ischemic encephalopathy almost invariably causes bilateral and symmetrical damage, often affecting the basal ganglia [ 25 ], as observed in our patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, leiomyomas attain moderate levels of [ 18 F]FDG uptake [17]. Angiomatosis, on the other hand, has been studied at other body locations and has been shown to demonstrate moderate [ 18 F]FDG expression [6][7][8][9]. The causal factor for such intense [ 18 F]FDG activity seems to be the metabolic potentiation effect of leiomyoma on the basis of the background of angiomatosis, giving rise to high [ 18 F]FDG uptake derived from the combination of both benign tumors potentiating [ 18 F]FDG expression.…”
Section: Discussionmentioning
confidence: 99%
“…In general, angiomatosis is not limited to a specific anatomical location but rather can present in various regions of the human body [6][7][8][9]. Within the female genital tract, this particular condition can manifest as discrete lesions, occur alongside other hemangiomas affecting the skin or other organs, or be a constituent of intricate syndromes such as the Klippel-Trénaunay-Weber syndrome [10].…”
Section: Introductionmentioning
confidence: 99%